«La housse partie» nelle tre versioni A, r e s (Carte Romanze, 2023)
This article compares the three versions of the fabliau La housse partie, starting with some observations about its literary motifs. The comparison of the three versions highlights interesting narratological and literary elements, and illustrates some peculiar characteristics of this fabliau, which is controversial because of its moralistic tones, of the protagonists and of the target audience. These debatable aspects are particularly interesting, as they reflect the same controversies about the genre itself. In conclusion, the analysis of the three versions allows for hypothesis on how this short story circulated in the Middle Ages, who it was addressed to and what its scope might have been.